Brain Activation Induced by Myopic and Hyperopic Defocus From Spectacles - Kang, Meng-Tian; Wang, Bo; Ran, An-Ran; Gan, Jiahe; Du, Jialing; Yusufu, Mayinuer; Liang, Xintong; Li, Shi-Ming; Wang, Ningli (Frontiers in Human Neuroscience, 2021)
Purpose: To assess neural changes in perceptual effects induced by myopic defocus and hyperopic defocus stimuli in ametropic and emmetropic subjects using functional magnetic resonance imaging (fMRI). Methods: This study included 41 subjects with a mean age of 26.0 ± 2.9 years. The mean spherical equivalence refraction was −0.54 ± 0.51D in the emmetropic group and −3.57 ± 2.27D in the ametropic group. The subjects were instructed to view through full refractive correction, with values of +2.00D to induce myopic defocus state and −2.00D to induce hyperopic defocus state. This was carried over in three random sessions. Arterial spin labeling (ASL) perfusion was measured using fMRI to obtain quantified regional cerebral blood flow (rCBF). Behavioral tests including distant visual acuity (VA) and contrast sensitivity (CS), were measured every 5 min for 30 min. Results: Myopic defocus induced significantly greater rCBF increase in four cerebral regions compared with full correction: right precentral gyrus, right superior temporal gyrus, left inferior parietal lobule, and left middle temporal gyrus (P < 0.001). The differences were less significant in low myopes than emmetropes. In the hyperopic defocus session, the increased responses of rCBF were only observed in the right and left precentral gyrus. Myopic defocused VA and CS improved significantly within 5 min and reached a plateau shortly after. Conclusion: This study revealed that myopic defocus stimuli can significantly increase blood perfusion in visual attention-related cerebral regions, which suggests a potential direction for future investigation on the relationship between retinal defocus and its neural consequences.